2015
DOI: 10.5812/cardiovascmed.4(2)2015.25223
|View full text |Cite
|
Sign up to set email alerts
|

Mid-ventricular variant of dobutamine-induced stress cardiomyopathy

Abstract: Introduction:Dobutamine stress testing is a commonly used modality in detecting and estimating the prognosis in coronary artery disease (CAD). Although it is well tolerated by most patients, adverse events have been reported. Rarely, transient wall motion abnormalities can occur in the absence of obstructive CAD to suggest stress cardiomyopathy.Case Presentation:We report a 48-year-old female with intermittent chest pain. Her physical exam, cardiac enzymes and transthoracic echocardiogram were unremarkable. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…Our review along with previous studies showed that the most common type of wall motion abnormality is apical type, followed by inverted type in patients younger than 55 years (12,13) or midventricular type of cardiomyopathy (14). A recent systematic review demonstrated that patients aged 45 years or less were less likely to have apical variant cardiomyopathy compared with patients aged 45 years or more (15).…”
Section: Literature and Discussionsupporting
confidence: 56%
“…Our review along with previous studies showed that the most common type of wall motion abnormality is apical type, followed by inverted type in patients younger than 55 years (12,13) or midventricular type of cardiomyopathy (14). A recent systematic review demonstrated that patients aged 45 years or less were less likely to have apical variant cardiomyopathy compared with patients aged 45 years or more (15).…”
Section: Literature and Discussionsupporting
confidence: 56%